What is the effectiveness of the shingles vaccine for preventing shingles in older adults?. Issue 2 (February 2018) - Wills, Stephen; Van Buskirk, John
Abstract : Bottom line : The zoster vaccine effectively prevents shingles in patients older than 60 years, with a number needed to treat (NNT) of about 60 to prevent 1 case of shingles over 3 years (SOR: B, systematic review including single RCT). A newly approved vaccine may be more effective than the current vaccine, with a NNT of 33 (SOR: B, based on a single RCT). All adults 60 years and older should be routinely offered the herpes zoster vaccine (SOR: C, evidence‐based expert opinion).